2016
DOI: 10.1093/ofid/ofw107
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Preemptive Antiviral Therapy Strategy Based on Combined Virological and Immunological Monitoring for Active Cytomegalovirus Infection in Allogeneic Stem Cell Transplant Recipients

Abstract: Preemptive antiviral therapy for active CMV infection in allogeneic stem cell transplant recipients guided by immunological and virological parameters minimizes the risk of recurrent viremia in a subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 26 publications
(36 reference statements)
0
39
0
Order By: Relevance
“…Studies of CMV immune monitoring in the HSCT population have shown clinical benefits in shortening antiviral treatment duration, predicting recurrent CMV reactivation and identifying patients at low risk of CMV complications or with lower CMV viral loads . Identifying patients that have developed reconstitution of CMV‐specific immunity using virological and immunological monitoring post‐HSCT significantly reduced the duration of anti‐CMV pre‐emptive treatment by a median of 9 days . HSCT recipients with inadequate reconstitution of CMV immunity at day +100 or at the end of first CMV reactivation were much more likely to experience recurrent CMV reactivation, implying that the period for CMV monitoring should be extended.…”
Section: Immune Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of CMV immune monitoring in the HSCT population have shown clinical benefits in shortening antiviral treatment duration, predicting recurrent CMV reactivation and identifying patients at low risk of CMV complications or with lower CMV viral loads . Identifying patients that have developed reconstitution of CMV‐specific immunity using virological and immunological monitoring post‐HSCT significantly reduced the duration of anti‐CMV pre‐emptive treatment by a median of 9 days . HSCT recipients with inadequate reconstitution of CMV immunity at day +100 or at the end of first CMV reactivation were much more likely to experience recurrent CMV reactivation, implying that the period for CMV monitoring should be extended.…”
Section: Immune Monitoringmentioning
confidence: 99%
“…Post-transplantation monitoring of CMV immunity in addition to serial quantitation of CMV DNA may better identify patients at risk of CMV complications. 2,16,17 New advances in diagnostic assays to rapidly assess CMV-specific immunity include the Quantiferon-CMV assay (Qiagen, Hilden, Germany), the T-Track CMV ELISPOT (Lophius Biosciences GmbH, Regensburg, Germany) and the T-SPOT. CMV assays (Oxford Immunotec, Abingdon, U.K.).…”
Section: Immune Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The logistical difficulties to provide the clinician with results within a short turnaround time must not be neglected. In fact, and despite various multicenter real‐life intervention studies based on the monitoring of CMV‐specific CMI led by our groups, no immune‐guided prevention approaches are still implemented in current daily practice at our institutions. In this sense, the design of new approaches to prevent post‐transplant CMV‐related events should first define the intended aims in terms of direct effects only (ie, CMV disease) or also encompassing long‐term indirect effects on graft and recipient outcomes (summarized in Table ) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by our group showed that patients treated preemptively with antivirals and expanding CMV-specific phosphoprotein (pp) 65 and immediate-early (IE)-1 interferon (IFN)-γ CD8 + T cells at levels >1 cell/μl at the time of CMV DNAemia clearance had a reduced risk of developing recurrent episodes of viremia, even using shorter courses of antiviral therapy [17]. We recently conducted a multicenter, closelymatched comparison-group study in which this assumption was found to be correct for a subset of patients [18]. Surely, the near future will witness the resurgence of the debate on whether universal prophylaxis with the new anti-CMV drugs or pre-emptive antiviral therapy must be the standard of care for the prevention of CMV-related clinical complications in allo-SCT recipients.…”
mentioning
confidence: 99%